THE EFFECT OF EMPLOYEE TRAINING ON SERVICE QUALITY - Dimas Aryo Baskoro; Damas Aryo Anggoro (Akademi Pariwisata Bunda Mulia, 2022)
ABSTRACT The purpose of this paper is to show how firms can enhance their service quality to increase customer satisfaction and thus customer loyalty? In answer to this question, three factors (i.e. employees, service quality, and customers) are critical to the success of service firms. The purpose of this research is to provide a research framework that examines relationships among employees, perceived service quality, customers.The design of this research applies a survey toward unit of analysis on shipping transportation service by interviewing the employee of PT. Humpuss Intermoda Transportasi, Tbk and also interviewing their clients as respondent for testing hypothesis. Meanwhile the required data consist of one variable independent which is employee training, one mediated variable which is service quality, and two variables dependent which are customer satisfaction and customer loyalty. The aggregate numbers of employees are 100 and clients 100 being respondent. Total respondent for this study are 200. Data analysis used in this research was consists of Pearson Correlation Test using SPSS as software. The result of this research concludes that three hypotheses are not supported, employee training had no effect to service quality, and then service quality had no effect to customer satisfaction and also to customer loyalty. Implications for management of the companies and directions for future research are discussed.